Antineutrophil cytoplasmic autoantibodies and anti-Saccharomyces cerevisiae antibodies in inflammatory bowel diseases - Zeki Mesut Yalın KILIÇ; Bilge TUNÇ; Selime AYAZ; Levent FİLİK; Semra AKTAŞ; Erkan PARLAK; Aysel ÜLKER (Turkish Journal of Gastroenterology, 2019)
-